A bifunctional fluorogenic rhodamine probe for proximity-induced bioorthogonal chemistry - Werther, Philipp; Möhler, Jasper; Wombacher, Richard (Chemistry - a European journal, 2017)
Bioorthogonal reactions have emerged as a versatile tool in life sciences. The inverse electron demand Diels-Alder reaction (DAinv) stands out due to the availability of reactants with very fast kinetics. However, highly reactive dienophiles suffer the disadvantage of being less stable and prone to side reactions. Herein, we evaluate the extent of acceleration of rather unreactive but highly stable dienophiles by DNA-templated proximity. To this end, we developed a modular synthetic route for a novel bifunctional fluorogenic tetrazine rhodamine probe that we used to determine the reaction kinetics of various dienophiles in a fluorescence assay. Under proximity-driven conditions the reaction was found to be several orders of magnitude faster, and we observed almost no background reaction when proximity was not induced. This fundamental study identifies a minimally sized fluorogenic tetrazine dienophile reactant pair that has potential to be generally used for the visualization of biomolecular interactions with temporal and spatial resolution in living systems.
Gesehen am 27.11.2018